Pengaruh Metode Bermain Peran Terhadap Keterampilan Berbicara pada Anak Usia 5-6 Tahun di PAUD Al - Fikhi Desa Bakal Dalam Kec. Talo Kecil Kab. Seluma - Revi Novia Sari; Asiyah Asiyah; Wiji Aziz Harimukti (UIN Fatmawati Sukarno Bengkulu, 2024)
This research was based on children aged 5-6 years in PAUD Al - Fikhi Bakal Village in Talo Kecil District, Seluma Regency, because there are still some children who are not 5 - 6 years old from the total number of 16 children, and the children also have Difficulty in responding and lack of stimulation means that children's speaking skills do not develop well. The aim of the research is to determine whether there is an influence of the role-playing method on speaking skills in children aged 5 - 6 years in PAUD Al - Fikhi, Bakal Dalam Village, Talo Kecil District, Seluma Regency. This research uses quantitative research with a type of experimental research, namely pre-experiment designs. The data collection technique uses the paired sample t-test formula (T Test) and is processed using the SPSS program. Because there are still external variables that influence the formation of the dependent variable. Based on the research results, it was found that there was an influence of the role-playing method on speaking skills in children aged 5 - 6 years in PAUD Al - Fikhi, Bakal Dalam Village, Talo Kecil District, Seluma Regency, with a significance value of 0.000 < α value, namely 0.05. The play method is a learning method for pre-school age children where children are invited to carry out activities together in the form of activities using tools or carrying out activities (games) either individually or together, which bring joy, pleasure and fun to children.